Immunohistochemical staining of normal, hyperplastic, and neoplastic adrenal cortex with a monoclonal antibody against alpha inhibin. Issue 2 (February 1998) - McCluggage, W G; Burton, J; Maxwell, P; Sloan, J M
Abstract : AIMS: To investigate the immunohisto-chemical staining of normal, hyperplastic, and neoplastic adrenal cortex with a monoclonal antibody against alpha inhibin. Also, to determine whether immunostaining with this antibody is useful in differentiating between adrenal cortical neoplasms and other tumours involving the adrenal gland that might mimic them. METHODS: Normal adrenal tissue (n = 20) and specimens from cases of adrenal hyperplasia (n = 13), adrenal cortical adenoma (n = 15), adrenal cortical carcinoma (n = 4), phaeochromocytoma (n = 8), and adrenal metastatic tumour (n = 7) were stained with a monoclonal antibody against the alpha subunit of human inhibin. RESULTS: Positive staining with the anti-alpha inhibin monoclonal antibody was seen in all normal adrenal glands. Immunoreactivity was largely confined to the inner cell layers of the adrenal cortex, with no staining of the adrenal medulla. All hyperplastic adrenal glands and adrenal cortical adenomas and carcinomas were also immunoreactive. The other tumours studied were negative. CONCLUSIONS: There is consistent immunoreactivity with the anti-alpha inhibin monoclonal antibody in normal adrenal cortex and in hyperplastic and neoplastic adrenal cortical lesions. In the normal adrenal cortex, positive staining is mainly confined to the zona reticularis. Other neoplasms involving the adrenal gland are negative. Immunohistochemical staining with anti-alpha inhibin monoclonal antibody, performed as part of a panel, may prove to be of value in the distinction between adrenal cortical carcinoma and phaeochromocytoma or metastatic tumour.